Hemostatic alterations in patients with obstructive sleep apnea: an observational study - Belaldavar, Basavaraj P.; J. S., Tejaswini; Soni, Samanvaya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Obstructive sleep apnoea (OSA) is characterized by repetitive partial or complete collapse of the upper airway during sleep, which results in disruptions of normal sleep architecture. It is associated with cardiopulmonary consequences like hypertension, myocardial infarction and stroke. Although the pathogenesis of this association remains unclear, an alteration in coagulability is suspected as a linkage. Hence, the present study aims at the reliability of Bleeding time, platelet count, PT, aPTT and INR to assess the effect on OSA patients’ cardiovascular system. Methods: This is an observational study done on 32 individuals diagnosed with OSA after level I polysomnography from time period of January 01, 2018 to December 31, 2018. The blood coagulation parameters studied for each individual were platelet count, bleeding time (BT), activated partial thromboplastin time (aPTT) and prothrombin time (PT/INR). Results: Out of a total 32 subjects, 17 (53.13%) were male and 15 (46.87%) were female. There is a significant difference in mean prothrombin time (p=0.022). Kruskal-Wallis test showed a significant difference in the median of the PT/INR (p=0.01) and AHI (p<0.001) for different categories of OSA. Prothrombin time is the only factor which is affecting the OSA. Conclusions: Patients with severe OSA may have elevated coagulability levels, particularly in the length of prothrombin time. The potential for anticoagulant and antiplatelet medications to reduce mortality in patients with OSA merits exploration, particularly for patients who are unwilling or unable to achieve full control of OSA with currently available treatment options.